Anomalous partitioning of water in coexisting liquid phases of lipid multilayers near 100% relative humidity. Issue 2 (14th December 2015) - Ma, Yicong; Ghosh, Sajal K.; Bera, Sambhunath; Jiang, Zhang; Schlepütz, Christian M.; Karapetrova, Evguenia; Lurio, Laurence B.; Sinha, Sunil K.
Abstract : Coexisting Lo and Ld domains minimize their domain wall mismatch energy by convergence of their d -spacings with increasing hydration. Abstract : Ternary lipid mixtures incorporating cholesterol are well-known to phase separate into liquid-ordered (Lo ) and liquid-disordered (Ld ) phases. In multilayers of these systems, the laterally phase separated domains register in columnar structures with different bilayer periodicities, resulting in hydrophobic mismatch energies at the domain boundaries. In this paper, we demonstrate via synchrotron-based X-ray diffraction measurements that the system relieves the hydrophobic mismatch at the domain boundaries by absorbing larger amounts of inter-bilayer water into the Ld phase with lower d -spacing as the relative humidity approaches 100%. The lamellar repeat distance of the Ld phase swells by an extra 4 Å, well beyond the equilibrium spacing predicted by the inter-bilayer forces. This anomalous swelling is caused by the hydrophobic mismatch energy at the domain boundaries, which produces a surprisingly long-range effect. We also demonstrate that the d -spacings of the lipid multilayers at 100% relative humidity do not change when bulk water begins to condense on the sample.